Improving Social Science Learning Outcomes Through the Number Head Together (NHT) Learning Model for Class IV Students at SDN 1 Ngawonggo - Marsiyah, Marsiyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study is to improve social studies learning outcomes through the Number Head Together (NHT) Learning Model for Grade IV students of SDN 1 Ngawonggo. The research method used is Classroom Action Research (PTK) as many as 2 cycles, with one meeting per cycle. The stages of the cycle are planning, execution, observation and reflection. The data collection procedure is through observation of educator activities, student activities and tests, then the data is analyzed using percentages in accordance with specified success criteria to determine student development. Based on the results of the study, it can be concluded that: (1) the percentage value of educator activity in cycle I is 79% and cycle II is 92%. (2) the percentage of activity of students in cycle I is 72% and cycle II is 89%. (3) the percentage value of the learning test results of students in the first cycle is 39.29% and in the second cycle 89.92%, students have completed classically. Thus, it can be concluded that the application of the NHT model can improve social studies learning outcomes of grade IV students of SDN 1 Ngawonggo.